Treatment Optimization of the Dyslipidemia in Type 2 Diabetes (Eurasian Medical Research Periodical, 2023)
This article studies the data on evaluation of the efficacy and safety of the drug Rozulip plus 10/10 mg in patients with type 2 diabetes mellitus with diabetic dyslipidemia. In addition, the research and basic results are given with numbers. The safety of examination was assessed by the number and type of registered adverse side effects, as well as by the detection of clinically significant changes in blood biochemical parameters.